Moderating Role of Marketing Audit on the Effect of Strategic Marketing Planning on Organisational Performance of Selected Quoted Consumer Goods Manufacturing Companies in Lagos - Seidu, A.J.; Akinlabi, B.H., Akinlabi, B.H.; Makinde, O.G. (Journal of Strategic Management, 2023)
Purpose: Recently, business uncertainty and pressures have challenged routine activities in consumer goods manufacturing companies (CGMC), resulting in dwindling performance due to their inability to respond swiftly and correctly to strategic marketing planning practices. However, proactive manufacturing businesses strive to evaluate their operational activities and thus put measures in place to improve their performance as a condition of continuous existence and future development. Such organisations analyse their routine functions periodically, through operational methods that allow the evaluation of their market strategy, current performance and function as management guides. The study therefore investigated the moderating role of Marketing Audit (MA) on strategic marketing planning and organisational performance of selected quoted consumer goods manufacturing companies in Lagos, Methodology: Survey research design was used for this study. The population was 594 staff in the sales and marketing departments of the selected CGMC in Lagos State, Nigeria. The study adopted total enumeration method. Purposive sampling technique was employed. Data were analysed using descriptive and inferential (multiple regression) statistics. Findings: The findings showed that marketing audit has a significant moderating effect on the effect of strategic market planning on organisational performance of selected quoted consumer goods manufacturing companies in Lagos State, Nigeria. Recommendations: The study therefore recommends that top management of CGMCs should review the companies MA on marketing strategy process of personnel with correct organizational values and attitudes.